- #1

- 6

- 0

hi, im trying to solve this equation and i would like some help.

i've done some of it already and i dont know how to go on from here.

[tex]z=-\frac{(4-4i)(\sqrt{6}-i\sqrt{2})}{i}\\ =-\frac{(4-4i)(\sqrt{6}-i\sqrt{2})-i}{i(-i)}=(4i+4)(\sqrt{6}-i\sqrt{2})\\ \hspace{6} r=\sqrt{4^{2}+4^{2}}=\sqrt{32}\hspace{6} and \hspace{6} v=\frac{\pi }{4}\hspace{6}[/tex]

the answer should be in this form a*pi/b

i've done some of it already and i dont know how to go on from here.

[tex]z=-\frac{(4-4i)(\sqrt{6}-i\sqrt{2})}{i}\\ =-\frac{(4-4i)(\sqrt{6}-i\sqrt{2})-i}{i(-i)}=(4i+4)(\sqrt{6}-i\sqrt{2})\\ \hspace{6} r=\sqrt{4^{2}+4^{2}}=\sqrt{32}\hspace{6} and \hspace{6} v=\frac{\pi }{4}\hspace{6}[/tex]

the answer should be in this form a*pi/b

Last edited: